PEMBINAAN PRESTASI ATLET REMAJA PENCAK SILAT PERSAUDARAAN SETIA HATI TERATE DI KECAMATAN MONTONG KABUPATEN TUBAN - NEDIANTO, (Jurnal Kesehatan Olahraga, 2016)
Exercise is any physical activity that is based on the struggle for control of yourself,others toovercomethe natural elements, thatif thecontestedmust beimplementedknights, so it is apowerfulmeans ofpersonaleducation. To achieve a high performance athletes have to have some things that talent, skill and motivation. PencakSilatis thefirstexercise. In Montong Tuban, there are various streams of Pencak Silat, one of them is Pencak Silat Instituation of Persaudaraan Setia Hati Terate. Persaudaraan Setia Hati Terate institution has good growth in achievement, in 2014 only has decreased performance in the championship PORKAB IPSI in Tuban.